2020
DOI: 10.1093/cid/ciaa491
|View full text |Cite
|
Sign up to set email alerts
|

First Reported Nosocomial Outbreak of Severe Acute Respiratory Syndrome Coronavirus 2 in a Pediatric Dialysis Unit

Abstract: Background Coronavirus disease 2019 (COVID-19) is a life-threatening respiratory condition caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and was initially detected in China in December 2019. Currently, in Germany over 140,000 cases of COVID-19 are confirmed. Here we report a nosocomial outbreak of SARS-CoV-2 infections in the pediatric dialysis unit of the University Hospital of Münster (UHM). Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
115
1
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 126 publications
(129 citation statements)
references
References 17 publications
4
115
1
9
Order By: Relevance
“…The PRISMA owchart of included studies is shown in Figure 1. Data from 18 studies were relevant for inclusion and are summarised in Tables 1 and 2. Twelve studies (63%) were conducted in China or Hong Kong, [10][11][12][13][14][15][16][17][18][19][20][21] three studies were performed in Europe [22][23][24] and three studies were carried out in the USA or Canada. [25][26][27] Nearly all studies reported data for specimens from the respiratory tract, although two studies analysed saliva, 21,22 one used stool and serum samples in addition to respiratory samples, 19 and one used both throat and anal swabs.…”
Section: Included Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…The PRISMA owchart of included studies is shown in Figure 1. Data from 18 studies were relevant for inclusion and are summarised in Tables 1 and 2. Twelve studies (63%) were conducted in China or Hong Kong, [10][11][12][13][14][15][16][17][18][19][20][21] three studies were performed in Europe [22][23][24] and three studies were carried out in the USA or Canada. [25][26][27] Nearly all studies reported data for specimens from the respiratory tract, although two studies analysed saliva, 21,22 one used stool and serum samples in addition to respiratory samples, 19 and one used both throat and anal swabs.…”
Section: Included Studiesmentioning
confidence: 99%
“…[12][13][14][15][16][17]22 Fourteen studies reported on the direct correlation of outcomes with Ct values. [10][11][12][13][14]16,17,20,[22][23][24][25][26][27] Three studies reported on the correlation of outcomes with viral load, determined using standard curves of Ct values versus RNA copy number, 15,19,21 and one study correlated outcomes with the inverse of Ct values, taken as a proxy for viral load. 18…”
Section: Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations